Taxonomic review of the Andean crab spiders genus Coenypha Simon, 1895 (Thomisidae: Stephanopinae) - Machado, Miguel; Previato, Thales; Grismado, Cristian J.; Teixeira, Renato (Zootaxa, 2023)
The genus Coenypha Simon, 1895 is composed of species distributed on the Southern Andean Region and Patagonia, and presents remarkable somatic morphologies, such as the flattened habitus, enlarged femora I, and a wide opisthosoma. Molecular and morphology-based phylogenies have revealed the close relationship of this genus with sympatric species previously assigned to Stephanopis O. Pickard-Cambridge, 1869. Our recent cladistic analysis extended such preliminary results in recovering numerous morphological characters as synapomorphies of a well-supported clade, thus justifying the transfer of all species of ‘Andean Stephanopis’ to Coenypha. In the present work, we provide a taxonomic review of these species, update their diagnoses, descriptions and illustrate them through detailed photographs. New distribution records are presented, the male of C. antennata (Tullgren, 1902) is described for the first time, and two new species are described based on both sexes (Coenypha trapezium sp. nov. and Coenypha foliacea sp. nov.). Stephanopis exigua (Nicolet, 1849) is considered a nomen dubium. Stephanopis verrucosa (Nicolet, 1849), Thomisus spectrum Nicolet, 1849, and T. pubescens Nicolet, 1849 are synonymized with Coenypha nodosa (Nicolet, 1849). The synonymy of Thomisus nicoleti Roewer, 1951 (a replaced name for T. cinereus Nicolet, 1849 due to a homonymy) with Misumenops temibilis (Holmberg, 1876) is rejected, and considered together with Stephanopis spissa (Nicolet, 1849), Thomisus variabilis Nicolet, 1849 and Stephanopis maulliniana Mello-Leitão, 1951, synonyms of Coenypha ditissima (Nicolet, 1849); Stephanopis badia Keyserling, 1880 is transferred to Sidymella Strand, 1942.